17 to 23: A novel complementary mini Y‐STR panel to extend the Y‐STR databases from 17 to 23 markers for forensic purposes. Issue 7 (13th January 2017) - Núñez, Carolina; Baeta, Miriam; Ibarbia, Nerea; Ortueta, Urko; Jiménez‐Moreno, Susana; Blazquez‐Caeiro, José Luis; Builes, Juan José; Herrera, Rene J.; Martínez‐Jarreta, Begoña; de Pancorbo, Marian M.
Abstract : A Y‐STR multiplex system has been developed with the purpose of complementing the widely used 17 Y‐STR haplotyping (AmpFlSTR Y Filer® PCR Amplification kit) routinely employed in forensic and population genetic studies. This new multiplex system includes six additional STR loci (DYS576, DYS481, DYS549, DYS533, DYS570, and DYS643) to reach the 23 Y‐STR of the PowerPlex® Y23 System. In addition, this kit includes the DYS456 and DYS385 loci for traceability purposes. Male samples from 625 individuals from ten worldwide populations were genotyped, including three sample sets from populations previously published with the 17 Y‐STR system to expand their current data. Validation studies demonstrated good performance of the panel set in terms of concordance, sensitivity, and stability in the presence of inhibitors and artificially degraded DNA. The results obtained for haplotype diversity and discrimination capacity with this multiplex system were considerably high, providing further evidences of the suitability of this novel Y‐STR system for forensic purposes. Thus, the use of this multiplex for samples previously genotyped with 17 Y‐STRs will be an efficient and low‐cost alternative to complete the set of 23 Y‐STRs and improve allele databases for population and forensic purposes.